Trends in the insurance business in the Czech republic - Jindrová, Pavla (Univerzita Pardubice, 2011)
This article brings an overview of development of the insurance industry in the Czech Republic in the period since the establishment of the independent the Czech Republic in 1993 till 2009. Into these parameters belong both general data such as the number of insurance companies and their distribution by type of insurance (life, nonlife, universal), and statistics of the several indicators of written premium during the monitored time interval.
Keywords: insurance; insurance company; written premium